Combined caudal‐superficial‐epigastric axial pattern flap and full‐thickness buccal mucosa graft for single‐stage preputial reconstruction in six dogs. (17th April 2018) - Massari, F.; Montinaro, V.; Buracco, P.; Romanelli, G.
Abstract : Objective: To describe the use of a caudal superficial epigastric flap in combination with a full‐thickness oral mucosal/submucosal graft for single‐stage reconstruction of extensive preputial defects in dogs. Materials and Methods: Medical records of dogs with extensive preputial defects either of traumatic origin or derived from tumour excision were reviewed. In all dogs, the prepuce was reconstructed using a full‐thickness oral mucosal/submucosal graft combined with a caudal superficial epigastric axial pattern flap during a single surgical procedure. Outcome was assessed by routine clinical examinations for 6 months postoperatively, and through telephone follow‐up thereafter. Results: Six dogs were included. The caudal superficial epigastric axial pattern flap healed without complications in all dogs, while the full‐thickness oral mucosal/submucosal graft failed in one dog. In this individual the skin flap underwent contracture 30 days after surgery and preputial advancement was required. One dog showed postoperative discomfort during urination, which was successfully managed with a Foley catheter and analgesic administration. Three dogs developed paraphimosis at 30, 80 and 90 days, respectively, and required further surgery. Long‐term results were good in all dogs. Clinical Significance: The use of a full‐thickness oral mucosal/submucosal graft combined with a caudal superficial epigastric axial pattern flap is feasible for single‐stage preputial reconstruction in dogs. Attention should be paid to create a sufficiently large preputial opening, in order to prevent paraphimosis.